Extending honneth’s shift in focus for critical theory - Giles, Douglas (Hybris, 2016)
Axel Honneth has called for a change of focus in Critical Theory "from the self-generated independence of systems to the damage and distortion of social relations of recognition." I argue that Honneth does not shift his methodological focus sufficiently to succeed in his goal of illuminating the social relations of recognition. Despite Honneth's shift to relations of recognition, he considers these relations in terms of the macrosocial Hegelian triad of social spheres of recognition. A deeper analysis of recognition behaviors shows they cannot be mapped exactly to these spheres. I conclude that the Hegelian triad of social spheres is an insufficient basis for an exploration of misrecognition behaviors. To understand misrecognition, we need to seek a picture of misrecognition that reflects the complex diversity of individuals' lived experiences and practices, gives sufficient attention to interpersonal recognition and misrecognition, and offers potential reasons for why individuals might engage in misrecognition behaviors.